Greco-Roman cities at the crossroads of cultures the 20th anniversary of Polish-Egyptian conservation mission Marina El-Alamein - Bąkowska-Czerner, Grażyna 1968-; Czerner, Rafał 1958- (Archaeopress Publishing Ltd, 2019)
These papers present research from different regions ranging from ancient Mauritania, through Africa, Egypt, Cyprus, Palestine, Syria, as well as sites in Crimea and Georgia. Topics include: topography, architecture, interiors and décor, religious syncretism, the importance of ancient texts, pottery studies and conservation
Keywords: Polish-Egyptian Archaeological and Preservation Mission at El Ashmunein; Civilization, Greco-Roman; Historic sites / Africa; Historic sites / Europe; Excavations (Archaeology) / Egypt / Mārīnā; Antike; Stadt; Mārīnā (Egypt) / Antiquities; Marina el-Alamein; Konferenzschrift -- 2015 -- Breslau